The Mediating Role of Fintech Adoption in the Relationship between Financial Literacy, Digital Literacy, and MSMEs’ Financial Performance - Reni Anggraeni; Agung Budi; Syifa Juliani Dwi Putri (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose — This study investigates whether fintech adoption acts as a mediating mechanism in linking financial literacy and digital literacy to the financial performance of MSMEs. Design/Methodology/Approach — A quantitative survey was conducted involving 400 MSME owners and managers in Banten Province, Indonesia. Data were analyzed using PLS-SEM to examine both direct and indirect relationships among constructs. Findings/Results — The findings indicate that financial literacy did not significantly improve financial performance directly (β = 0.083; p = 0.225). In contrast, digital literacy positively influenced financial performance (β = 0.241; p < 0.001). Both financial literacy (β = 0.318; p < 0.001) and digital literacy (β = 0.354; p < 0.001) significantly increased fintech adoption. Fintech adoption also had a significant positive impact on financial performance (β = 0.401; p < 0.001). Mediation testing confirmed that fintech fully mediated the financial literacy–performance relationship and partially mediated the digital literacy–performance relationship. Originality/Value — This study highlights fintech adoption as a strategic mechanism that transforms literacy capabilities into measurable financial outcomes, extending the understanding of MSME performance in emerging digital economies.